2014
DOI: 10.3390/cryst4020152
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Effects on Photoluminescence of CdSe Nanoparticles in a PMMA Film

Abstract: External electric field effects on spectra and decay of photoluminescence (PL) as well as on absorption spectra were measured for CdSe nanoparticles in a poly(methyl methacrylate) (PMMA) film. Electrophotoluminescence (E-PL) spectra as well as electroabsorption spectra show a remarkable Stark shift which depends on the particle size, indicating a large electric dipole moment in the first exciton state. The E-PL spectra also show that PL of CdSe is quenched by application of electric fields, and the magnitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
(82 reference statements)
1
1
0
Order By: Relevance
“…Therefore, the modulation of photoresponse could be attributed to the effects of light illumination and the lateral electric field that is simultaneously applied to the PCBM-doped BLMs. It has been reported that the photoluminescence and absorption of CdSe nanoparticles that are incorporated into a polymer film would be changed due to the external electric field . Similar behaviors have also been observed in other systems that comprise nanoparticles. Therefore, we conclude that the electrical field introduced by the lateral Al electrodes in our experimental setup may have altered the optical characteristics of the PCBM molecules in the BLMs, leading to a phototransistor-like transmembrane current response that is regulated by the lateral bias.…”
Section: Results and Discussionsupporting
confidence: 82%
“…Therefore, the modulation of photoresponse could be attributed to the effects of light illumination and the lateral electric field that is simultaneously applied to the PCBM-doped BLMs. It has been reported that the photoluminescence and absorption of CdSe nanoparticles that are incorporated into a polymer film would be changed due to the external electric field . Similar behaviors have also been observed in other systems that comprise nanoparticles. Therefore, we conclude that the electrical field introduced by the lateral Al electrodes in our experimental setup may have altered the optical characteristics of the PCBM molecules in the BLMs, leading to a phototransistor-like transmembrane current response that is regulated by the lateral bias.…”
Section: Results and Discussionsupporting
confidence: 82%
“…The result supports the formation of nanoparticles and hence an increase in band gap compared to bulk CdSe.Akey et al (2012) [115] have studied anomalous photoluminescence Stokes shift in CdSe nanoparticle and carbon nanotube hybrids. Nakabayashi et al [116] have investigated the external electric field effects on spectra and decay of photoluminescence (PL) as well as on absorption spectra of CdSe nanoparticles in a poly(methyl methacrylate) (PMMA) film. Electrophotoluminescence (E-PL) spectra as well as electroabsorption spectra show a remarkable Stark shift which depends on the particle size, indicating a large electric dipole moment in the first exciton state.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…External electric field effects on optical spectra have been extensively used in molecular spectroscopy to examine electronic structures in the excited states. The so-called electroabsorption (E-A) spectra provide unique information about the difference in electric dipole moment (μ) and molecular polarizability (α) between the ground state and the excited state. E-A measurements have been used by many research groups to investigate the electric-field effects on the electronic states in II–VI semiconductor QDs across the visible spectral range (400–800 nm), such as CdS, CdSe, ZnSe, CdS x Se 1– x , etc. E-A spectra in the near-infrared region were also reported for PbS and PbSe. , Narrow transition line widths inherent in QDs, coupled with large Stark shift, should result in electro-optic modulation devices with even greater efficiency. In addition to possible device applications, the quantum-confined Stark effect (QCSE) can be used to prove the nature of the excited states of QDs.…”
Section: Introductionmentioning
confidence: 99%